Kajian Nilai Pendidikan pada Tari Betangas - Anindri, Mutia (Program Studi Pendidikan Tari FBS UNJ, 2021)
This study aims to describe and analyze the form of choreography, make-up, clothing and the educational value of the Betangas dance. Besides that, this research was conducted to preserve the culture in Banyuasin Regency as a form of appreciation, the Betangas dance was created from a choreographer's interest in the Betangas traditional procession for prospective brides. Betangas is a traditional steam bath process carried out by every bride and groom before entering their wedding day. Apart from being literally Betangas, this is to eliminate body odor, so that on the wedding day the bride and groom will be fresher, more beautiful and radiant to enter a new phase of life. Betangas dance was created to strengthen the identity of Banyuasin Regency. In this study, used a qualitative approach with descriptive analysis method, data collection techniques in the form of observation, interviews, documentation techniques and literature study. Through this method, the researcher will discuss more deeply about the choreographic structure of the Betangas dance in the study of Ethnochoreology and also a more accurate explanation regarding the make-up and clothing of the Betangas dance. The results of the study stated that the movements in the Betangas dance fall into several categories, namely, gesture, locomotion, button signal with two designs, symmetrical and asymmetrical. The make-up used in the Betangas dance uses corrective make-up and is wrapped in closed dance clothing in accordance with the influence of Malay culture which has Islamic nuances and lives in the Banyuasin district community. In Betangas dance, there are various cultural and educational values that are implied in symbolic movements that are supported by the meanings contained in the use of props and costumes used by the dancers.